NILAI RELIGIUS DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Nanda Saputra Saputra (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2020)
This research is a library research, which is a research that utilizes library resources to obtain research data. Data collection techniques in this research are symbolic and semantic reading and recording information contained in data using data cards. The data that has been collected is then analyzed using the Hermeneutics technique which is to analyze by interpreting and interpreting the language in the novel. Based on the results of this descriptive study, it was found that the religious values contained in the novel The Split Month in the American Sky include: Aqeedah (Faith) values which include: Faith in God, Faith in angels, Faith in the Book, Faith in the Prophets and Apostles, Faith in the End Times, Faith in Qada 'and Qadar. Shari'ah values (Worship) which include: reading the Qur'an, alms, and remembrance of Allah. Akhlaq values (moral character) include: the value of patience, gratitude, and filial piety to parents.